2020
DOI: 10.3390/metabo10040150
|View full text |Cite
|
Sign up to set email alerts
|

Sink/Source Balance of Leaves Influences Amino Acid Pools and Their Associated Metabolic Fluxes in Winter Oilseed Rape (Brassica napus L.)

Abstract: Nitrogen remobilization processes from source to sink tissues in plants are determinant for seed yield and their implementation results in a complete reorganization of the primary metabolism during sink/source transition. Here, we decided to characterize the impact of the sink/source balance on amino acid metabolism in the leaves of winter oilseed rape grown at the vegetative stage. We combined a quantitative metabolomics approach with an instationary 15N-labeling experiment by using [15N]L-glycine as a metabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Therefore, the further development of 15 N-based fluxomics to explore AA metabolism in crops would be highly beneficial. For instance, the recent use of scalable metabolic flux modeling after 15 N-glycine labeling showed that metabolic fluxes associated with de novo biosynthesis of proline and valine were strongly affected by leaf sink/source balances in Brassica napus (Dellero et al, 2020b). Future work should focus on developing more detailed and complete isotopic models of compartmented AA metabolism in crops under normal and low N conditions to identify new targets to improve NUE (and abiotic stress tolerance).…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…Therefore, the further development of 15 N-based fluxomics to explore AA metabolism in crops would be highly beneficial. For instance, the recent use of scalable metabolic flux modeling after 15 N-glycine labeling showed that metabolic fluxes associated with de novo biosynthesis of proline and valine were strongly affected by leaf sink/source balances in Brassica napus (Dellero et al, 2020b). Future work should focus on developing more detailed and complete isotopic models of compartmented AA metabolism in crops under normal and low N conditions to identify new targets to improve NUE (and abiotic stress tolerance).…”
Section: Concluding Remarks and Perspectivesmentioning
confidence: 99%
“…This can happen because either they are being used less or being produced more. It should be noted that variations of amino acid pool sizes are clearly not always correlated with intuitive variations of their associated metabolic fluxes [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…El Moukhtari et al, 2020). Multi-level analyses and flux modeling demonstrated that different plant species rely on different regulatory mechanisms of either transcriptional regulation or modulation of enzyme activities to shift the balance between proline biosynthesis, consumption, and degradation toward proline accumulation (AbdElgawad et al, 2015;Hildebrandt, 2018;Dellero et al, 2020). Proline is synthesized from glutamate and also degraded to glutamate via the common intermediate glutamate-5-semialdhyde (GSA), which is in spontaneous equilibrium with pyrroline-5-carboxylate (P5C, Figure 1).…”
Section: P5cmentioning
confidence: 99%
“…Therefore, in order to improve crop performance under stress conditions, a lot of research has been dedicated to understand the molecular basis of proline accumulation and the role of this amino acid in plant acclimation and stress tolerance ( Szabados and Savoure, 2010 ; Forlani et al, 2019 ; El Moukhtari et al, 2020 ). Multi-level analyses and flux modeling demonstrated that different plant species rely on different regulatory mechanisms of either transcriptional regulation or modulation of enzyme activities to shift the balance between proline biosynthesis, consumption, and degradation toward proline accumulation ( AbdElgawad et al, 2015 ; Hildebrandt, 2018 ; Dellero et al, 2020 ). Proline is synthesized from glutamate and also degraded to glutamate via the common intermediate glutamate-5-semialdhyde (GSA), which is in spontaneous equilibrium with pyrroline-5-carboxylate (P5C, Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%